REVIEW OF VISEAN UNCONVENTIONAL RESERVOIRS WITHIN DNIPRO-DONETS DEPRESSION AND COMPARISON TO NORTH AMERICAN UNCONVENTIONAL FORMATIONS - KRUHLOV, Bohdan; LEVONIUK, Serhii; IURAS, Sviatoslav; KARPENKO, Ivan (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. Modern advances in the extraction of hydrocarbons from shale and tight formations, namely improved horizontal drilling technologies and multi-stage hydraulic fracturing at economically viable costs, are opening up new horizons for oil and gas exploration and development around the world. The importance of shale oil and gas has sparked interest around the world following the great success of production in North America. This article is a continuation of a series of publications on the study of Visean unconventional reservoirs within Dnipro-Donets Depression. In this paper, the Visean sediments, namely the Lower Visean carbonate plate of the XIII MFH (horizons V-24-25), and the "Rudov Beds", siliceous calcified organic-rich shales (V-23) within the identified prospective zones of the Dnipro-Donets Basin (DDB), are considered for their unconventional reservoir development potential using the method of analogy with successful North American formations.Methods. Key geological and geochemical parameters were compared with the selected analogues, namely, geological age, sedimentation conditions, lithology and sediment thickness, geochemical data (total organic carbon (TOC), vitrinite reflectance (Ro), rock generation properties according to pyrolytic studies and rock maturity), mineralogical composition and porosity.Results. According to this study, the Visean unconventional deposits within DDB clearly correlate with the most productive gas fields from unconventional reservoirs (shales, organic-rich carbonates) in North America. The depth and geological position of the Visean unconventional targets are generally comparable to or slightly higher than their North American counterparts based on available data; sediment thicknesses are in similar ranges. In terms of mineralogical composition, namely X-ray diffraction (XRD) analysis, the ore beds are similar to the Barnett and Woodford shales, and the V-24-25 carbonate horizons correspond to the Eagle Ford Formation. The high average TOC content of the V-23 horizon (up to 10% by weight) is comparable to the Bakken and Woodford shales.Сonclusions. The geological and geochemical parameters of the Visean horizons considered in this paper are promising in terms of the prospects for the development of unconventional reservoirs to increase Ukraine's energy resource base. However, in order to draw conclusions about the economic profitability of the development of the studied objects, a more detailed study is required, taking into account the results of drilling and testing after multistage hydraulic fracturing.
Keywords: source rock; unconventional reservoirs; total organic carbon; shale gas; rudov beds; thermal maturity